2003
DOI: 10.1149/1.1606455
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Two-Dimensional One-Phase Model for Analysis of the Anode of a DMFC

Abstract: An isothermal two-dimensional liquid phase model for the conservation of mass, momentum, and species in the anode of a direct methanol fuel cell ͑DMFC͒ is presented and analyzed. The inherent electrochemistry in the DMFC anode active layer is reduced to boundary conditions via parameter adaption. The model is developed for the case when the geometry aspect ratio is small, and it is shown that, under realistic operating conditions, a reduced model, which nonetheless describes all the essential physics of the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 23 publications
0
50
0
Order By: Relevance
“…The energy conversion process of DMFC can be modeled by a coupling of the governing equations of continuity, momentum and species transportation, as mentioned in Equations (3), (10) and (12). The source term S m and S mon in Section 2.2.…”
Section: Numerical Implementationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy conversion process of DMFC can be modeled by a coupling of the governing equations of continuity, momentum and species transportation, as mentioned in Equations (3), (10) and (12). The source term S m and S mon in Section 2.2.…”
Section: Numerical Implementationsmentioning
confidence: 99%
“…The flow fields can be determined by solving Equations (3) and (10). The obtained flow rate − → v is then applied in Equation (12) to determine the convection and diffusion of species. Because of the technical limitations, not all the the parameters involved in governing equations can take a definitive value from experimental measurements.…”
Section: Numerical Implementationsmentioning
confidence: 99%
See 1 more Smart Citation
“…15, it is generally assumed that no CO 2 , in either the liquid or gas phase, can permeate through the membrane. 1,6,7,[28][29][30][31] Some authors have studied this experimentally and have found that CO 2 does indeed cross over through the membrane to the cathode and the amount present may be negligible 32 or nonnegligible 33,34 based on the operating conditions. In this paper, however, CO 2 crossover was neglected, and should provide an indication of the most aggressive requirements for CO 2 removal.…”
Section: 2223mentioning
confidence: 99%
“…Since the membranes are basically identical, the same can be said of the membrane models [121,174,[235][236][237][238][239][240][241][242][243]. A benefit of DMFCs is that liquid water exists on both sides of the membrane (in most cases at high enough current densities), and thus it remains liquidequilibrated throughout.…”
Section: Direct-methanol Fuel Cellsmentioning
confidence: 99%